2011
DOI: 10.3389/fnagi.2011.00018
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory Information Processing in the Aging Population

Abstract: While it is well known that skin physiology – and consequently sensitivity to peripheral stimuli – degrades with age, what is less appreciated is that centrally mediated mechanisms allow for maintenance of the same degree of functionality in processing these peripheral inputs and interacting with the external environment. In order to demonstrate this concept, we obtained observations of processing speed, sensitivity (thresholds), discriminative capacity, and adaptation metrics on subjects ranging in age from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
82
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 68 publications
8
82
0
Order By: Relevance
“…This supports the claim of Zheng et al [34] mentioned above, regarding plasticity of the central nervous system in the elderly. In addition, the fact that only independent participants with general good health participated in the present study may also contribute to this result.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This supports the claim of Zheng et al [34] mentioned above, regarding plasticity of the central nervous system in the elderly. In addition, the fact that only independent participants with general good health participated in the present study may also contribute to this result.…”
Section: Discussionsupporting
confidence: 82%
“…This plasticity may compensate for the sensory processing changes and should be taken into consideration in intervention programs for the elderly, which also focus on function maintenance [34] .…”
Section: Discussionmentioning
confidence: 99%
“…The measure that we currently use to describe the impact that conditioning stimuli have on some aspect of sensory discriminative capacity -but most often amplitude discriminative capacity -is the adaptation metric, a value which has been demonstrated to be relatively constant across a large age spectrum of healthy controls (Zhang et al, 2011b). However, the adaptation metric for a number of neurological conditions has been demonstrated to be reduced or below normative values.…”
Section: Introductionmentioning
confidence: 98%
“…Previously, we reported that the ability of an individual to perceive the difference between two simultaneouslydelivered vibratory stimuli to the skin can be impacted significantly by relatively brief (0.2 to 2 s) periods of preexposure to conditioning stimuli (Folger et al, 2008;Francisco et al, 2011;Tannan et al, 2006Tannan et al, , 2007Tannan et al, , 2008Tommerdahl et al, 2007aTommerdahl et al, , 2007bTommerdahl et al, , 2010aZhang et al, 2008Zhang et al, , 2009Zhang et al, , 2011aZhang et al, , 2011b. The measure that we currently use to describe the impact that conditioning stimuli have on some aspect of sensory discriminative capacity -but most often amplitude discriminative capacity -is the adaptation metric, a value which has been demonstrated to be relatively constant across a large age spectrum of healthy controls (Zhang et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the individuals included in our study were recruited from an old population and a similar study should also be conducted in younger subjects to evaluate if these findings are similar for all subjects with thumb CMC OA. In fact, discrepancies on pressure pain sensitivity can be related to age-related changes in anatomical, physiological, and biomechanical structures of peripheral pathways involved in pain processing [20,49].…”
Section: Central Sensitization In Patients With Thumb Cmc Oamentioning
confidence: 99%